Estudio de pre factibilidad para la producción de papaya hawaiana carica papaya en el cantón Arenillas - Rodríguez Ochoa, Marco Edison (2012)
The basic study of pre feasibility Hawaiian papaya production identified new investment op-tions to benefit the agricultural sector in the El Oro province, in this study were re-fined in greater detail, aspects, technical, market and economic, was included in the study, among others, the socioeconomic aspects of the study area environment, market analy-sis identifying the main variables that affect their behavior, defining in princi-ple alternative location and all restrictions that may affect, selecting a adequate technical model, and finally determining the cost of producing an acre of Hawaiian papaya in Arenillas city, breakeven and benefit - cost relation.Since the pre-feasibility studies are used as a bargaining tool with financial institu-tions or potential investors, at this level may include details regarding the sources of fund-ing. Upon completion of the prefeasibility study we hope, then, or improve the level of information to make a more considered decision and move to the feasibility study or pro-ceed to final design to run it, or abandon the project temporarily or permanently by not sub-mitting comparative advantages that justify its implementation. It should be noted that the pre-feasibility study conducted to define a single alternative to be studied if necessary, with greater rigor in the feasibility stage.In Chapter I "Market Research" Ecuador is a major producer of tropical fruits and has an infrastructure already assembled for export, mainly bananas. The agricultural conditions of the project area are well suited for the production of these fruits. In the international market re-search methodology by CAN (Competitive Analysis of Nations), it follows that the country has revealed comparative advantages for production and export of tropical fruits. This is an item has a great market appeal due to the experiencing dynamic growth. The market of Papa-yas is growing quickly and is spreading at the level of European Union countries, especial-ly the German market.In Chapter II "Technical Study" Analysis of the study site environment, knowledge of use and development of land allowed us to analyze not only the agronomic traits, but facilitated the understanding of cropping systems and types of use , performance, relationships and main evolution trends, and the set of social, economic and cultural population. As the varia-bles that influence the production of Hawaiian papaya cultivation in the study area, the use of technology packages to farmers in the area and the perception for this cultivate non tradi-tional.In Chapter III "Economic Survey" has as its objective the determination of economic re-sources to the production process requires not only indicate the sources and the condi-tions under which these would occur, schedule of activities, so it is a basic tool, because that allows us to analyze production costs based on benefit / cost and the equilibrium point.